Cognitive Ontology and Region- versus Network-Oriented Analyses. - Klein, Colin (Philosophy of Science, 2012)
The interpretation of functional imaging experiments is complicated by the pluripotency of brain regions. As there is a many-to-one mapping between cognitive functions and their neural substrates, region-based analyses of imaging data provide only weak support for cognitive theories. Price and Friston argue that we need a 'cognitive ontology' that abstractly categorizes the function of regions. I argue that abstract characterizations are unlikely to be cognitively interesting. I argue instead that we should attribute functions to regions in a context-sensitive manner. I review recent meta-analyses that approach fMRI data in this light and argue that they have revisionary potential.